Paradoxes and inconsistencies in the law - Perez, Oren; Teubner, Gunther (Hart, 2006)
Is law paradoxical? This book seeks to unravel the riddle of legal paradoxes. It focuses on two main questions: the nature of legal paradoxes, and their social ramifications. In exploring the structure of legal paradoxes, the book focuses both on generic paradoxes, such as those associated with the self-referential character of legal validity and the endemic incoherence of legal discourse, and on paradoxes that permeate more restricted fields of law, such as contract law, euthanasia, and human rights (the prohibition of torture). The discussion of the social effects of legal paradoxes focuses on the role of paradoxes as drivers of legal change, and explores the institutional mechanisms that ensure the stability of the law, in spite of its paradoxical makeup. The essays in the book discuss these questions from various perspectives, invoking insights from philosophy, systems theory, deconstruction and economics.